“A school where you relearn to be proud of who you are.” - Emanuelle Dufour (Recherches amérindiennes au Québec, 2016)
Since its opening in Odanak in 2011, Kiuna Institution is the only postsecondary institution run by and for Quebec’s First Nations. Inspired by its predecessor, La Macaza’s Manitou College (1973-1976), and rooted in a similar ideology as the American Tribal Colleges and Universities (TCUs), the institute focuses on the establishment of cultural security (protection of the culture) and continuity within its programs and services. However, the introduction of Indigenous perspectives and curricula within the provincial education system raises a number of conceptual and logistical challenges. Can postsecondary institutions provide a supportive environment for the development of indigenous identities? Can the adaptation of curricular programs foster the perseverance and success of First Nations students? Based on testimonies and experiences of First Nations’ students, graduates and professionals collected between 2013 and 2015, this article analyzes the different components and cultural approaches integrated within Kiuna’s Social Science program and emphasizes the impact of cultural security within the collegial success of First Nations students. Depuis son ouverture en 2011 à Odanak, l’Institut collégial Kiuna constitue le seul établissement postsecondaire conçu par et pour les Premières Nations du Québec. Il s’inscrit dans la ligne directe de son prédécesseur, le Collège Manitou de La Macaza (1973-1976) et des Tribal Colleges and Universities (TCU) américains en matière de sécurité et de continuité culturelles. Or, l’introduction de perspectives autochtones et de cursus adaptés au sein du système d’éducation provincial pose un certain nombre de défis conceptuels et logistiques. L’établissement postsecondaire peut-il s’avérer un environnement favorable au développement identitaire des étudiants autochtones ? L’adaptation de programmes postsecondaires peut-elle contribuer à la persévérance et à la réussite des étudiants des Premières Nations ? Cet article vise à analyser les dispositifs inscrits au sein du projet ...